Staurosira magallanesica, a replacement name for Staurosira patagonica - García, María Luján (2018)
Staurosira patagonica M.L.Garcia, Maidana, Ector & E.Morales described a new species found in material of Maar Magallanes, Patagonia, Argentina and other lakes in southern Patagonia. This new species was analysed in detail by light and electron microscopy and a comprehensive description is given in Garcia et al. (2017: 107, 114, figs 2-45). However, this name is a later homonym of Staurosira patagonica Cleve, 1882. If we compare our species to Cleve’s illustration (Cleve 1882: pl. 16: fig. 13), we can easily differentiate the two by their general valve outline and morphometric data. As pointed out by Garcia et al. (2017), re-examination of the type material of members of the Fragilariaceae is needed to confirm identities, establish taxonomic boundaries and to facilitate identification, and this is also the case with Staurosira patagonica Cleve. A new name is, however, required for Staurosira patagonica M.L.Garcia, Maidana, Ector & E.Morales as it is an illegitimate name: Staurosira magallanesica M.L.Garcia, Maidana, Ector & E.Morales nom. nov. Replaced synonym: Staurosira patagonica M.L.Garcia, Maidana, Ector & E.Morales Nova Hedwigia, Beiheft 146: 107, 114, figs 2-45, 2017, nom illeg., non Staurosira patagonica Cleve 1882 Öfversigt af Kongliga Svenska Vetenskaps-Akademiens Förhandlingar 38(10): 13, pl. 16: fig. 13, 1882 ‘1881’. Etymology: we have derived the specific epithet from the name of the paleolake Maar Magallanes where this new species was found for the first time by N.I. Maidana (Maidana & Corbella 1997).